Transfusion-Refractory Warm Autoimmune Hemolytic Anemia with Dual Direct Antiglobulin Test Positivity and Marked Monocytosis in an Elderly Patient: A Case Report - I Gusti Ngurah Bayu Paramartha; Dewa Gde Agung Wikananda Besang; Desak Agung Indah Praharsini Dewi (HM Publisher, 2026)
Warm autoimmune hemolytic anemia represents a significant clinical challenge in adult hematology, with corticosteroid refractoriness occurring in approximately thirty to forty percent of cases. Management becomes substantially more complex in elderly patients with multiple comorbidities, where standard immunosuppressive therapy frequently fails and alternative therapeutic strategies become necessary. A sixty-three-year-old male with three months of documented warm autoimmune hemolytic anemia presented with acute hemolytic crisis manifested by severe anemia (hemoglobin declining from five point three to four point four grams per deciliter over four days) and accelerated hemolysis. Direct antiglobulin testing demonstrated dual positivity with immunoglobulin G one plus and complement component three-d two plus, indicating complement-mediated hemolysis. Notably, marked monocytosis ranged from seventy to seventy-four percent across serial complete blood counts. The patient demonstrated rapid immunosuppressive treatment failure with escalated triple therapy (methylprednisolone, mycophenolate mofetil, azathioprine) failing within four days of initiation. Transfusion refractoriness was evident despite premedication protocols. Concurrent medical conditions included hypertensive heart disease with documented coronary artery disease, newly diagnosed type two diabetes mellitus with suboptimal glycemic control, benign prostatic hyperplasia requiring catheterization, and clinical immunosuppression complications. The patient was referred to a tertiary academic medical center for advanced therapeutic decision-making. In conclusion, this case illustrates the diagnostic and therapeutic complexity of warm autoimmune hemolytic anemia with complement activation in an elderly population, highlighting the necessity for rapid escalation to advanced therapeutic modalities beyond conventional immunosuppression when clinical deterioration occurs despite maximal standard therapy.